Development of Volleyball Match Statistics Applications - Pratama, Galih; wahyudi, agung; Nasuka, Nasuka (Journal of Physical Education and Sports, 2025)
The purpose of this research is to create a volleyball match statistics application and determine the effectiveness of the product. The research method used is research and development. Before the product trial, this product has been validated by volleyball experts and media experts. The assessment conducted by volleyball experts received an average score of 86.7% with "Good" criteria, while the validation of media experts obtained the same average score of 86.7% with "Good" criteria. After validation, it was continued with product trials which were divided into 2 stages, namely small-scale trials and large-scale trials. The small-scale trial received an average score of 88.89% which means it is in the "Good" assessment category. The large-scale trial received an average score of 88.75% in the "Good" category. The effectiveness test was conducted to obtain information whether this match statistics application was more effective than manual statistical records. In this test, an assessment comparison was made between manual statistics and statistical applications, with the following results: the average effectiveness of manual statistics is 46.3% and the statistical application is 84.3%. In conclusion, the volleyball match statistics application is more effective than the manual statistics record.